MATERNAL HEALTH CARE PRACTICES OF LOTHA NAGA TRIBAL WOMEN IN INDIA - Humtsoe, Mhadeno Y; Soundari, M Hilaria (PEOPLE: International Journal of Social Sciences, 2019)
Tribal Women in India are more privileged in various ways as in comparison with the women of caste hierarchy. However, due to geographic isolation, they are deprived of access to basic amenities like livelihood opportunities, education, health, and sanitation. The twin factors of distance and cost of intensive maternal health care expenses hinders the tribal women in accessing to the health care services. For this reason, the traditional health care practitioners are profoundly preferred and they have been the largest maternal health care providers to the tribal women. The Maternal Mortality Rate (MMR) in India was 174 in 2015 (WHO, 2018) and the MMR in the State of Nagaland accounts of 160 (GOI-UNDP Report Nagaland, 2016). The Nagaland State also indicates as the lowest and poorest in maternal health care among the Northeastern States in India with an institutional delivery of only 33 percent. The institutional delivery in Wokha District of Nagaland accounts of 34 percent (NFHS-4, 2016). Thus, the study has been undertaken with an objective to portray the maternal health care status of the Lotha tribal women; to describe the maternal health care practices among Lotha tribal women; and to determine the health care infrastructure in the study areas. The Sequential Explorative Research Design has been adopted, and the study ponders on the maternal health care practices of Lotha Tribal women residing in Yanpha and Old Ralan Villages of Wokha District in the State of Nagaland, India. The study therefore, intends to contribute in achieving Sustainable Development Goals (SDGs) at the national and global level.